Backward Linkages in the Ready Made Garment Industry of Bangladesh: Appraisal and Policy Implications - Habib, Mohammed Rakib Ibne (UI Scholars Hub, 2009)
In global apparels market, international buyers will place on order with price competitiveness along with lead time. For Bangladesh, lead time is fast emerging as a serious bottleneck. Backward linkages are playing major part of a garment industry to reduce lead time and offer competitive price in the international market. It is inevitable that one of the major issues of success in readymade garment (RMG) industry in Bangladesh intensely depends on backward lingkages status, support, and strategic formulation. This paper will briefly discuss the present condition of backward integration comparison to other countries, impact of lead time, why lead time get priorities, process of short lead time and how central backward linkages in the short-run considered central bonded warehouse (CBW) in the RMG sector. Finally this paper will focus on policy implication on backward linkage sub-sectors, scheme of intensifiying central bonded warehouse (CBW) facility, procedure for short lead time in respect of free trade apparel market.